Enteral tolerance in critically ill patients - Hiroomi Tatsumi (Journal of Intensive Care, 2019)
Abstract Enteral nutrition (EN) can maintain the structure and function of the gastrointestinal mucosa better than parenteral nutrition. In critically ill patients, EN must be discontinued or interrupted, if gastrointestinal complications, particularly vomiting and bowel movement disorders, do not resolve with appropriate management. To avoid such gastrointestinal complications, EN should be started as soon as possible with a small amount of EN first and gradually increased. EN itself may also promote intestinal peristalsis. The measures to decrease the risk of reflux and aspiration include elevation the head of the bed (30° to 45°), switch to continuous administration, administration of prokinetic drugs or narcotic antagonists to promote gastrointestinal motility, and switch to jejunal access (postpyloric route). Moreover, the control of bowel movement is also important for intensive care and management. In particular, prolonged diarrhea can cause deficiency in nutrient absorption, malnutrition, and increase in mortality. In addition, diarrhea may cause a decrease the circulating blood volume, metabolic acidosis, electrolyte abnormalities, and contamination of surgical wounds and pressure ulcers. If diarrhea occurs in critically ill patients on EN management, it is important to determine whether diarrhea is EN-related or not. After ruling out the other causes of diarrhea, the measures to prevent EN-related diarrhea include switch to continuous infusion, switch to gastric feeding, adjustment of agents that improve gastrointestinal peristalsis or laxative, administration of antidiarrheal drugs, changing the type of EN formula, and semisolidification of EN formula. One of the best ways to success for EN management is to continue as long as possible without interruption and discontinuation of EN easily by appropriate measures, even if gastrointestinal complications occur.